2020
DOI: 10.1155/2020/3967641
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Tensile Properties of Handmade Sida rhombifolia Paper

Abstract: This study focuses on the production and characterization of biodegradable handmade paper from the Sida rhombifolia plant (SRP) cellulose. Sida rhombifolia plant is a seasonal plant that grows in the equatorial and tropical climates. The studies carried out on this SRP were aimed at investigating the methods required for the production of handmade paper from SRP plant and also at determining the tensile strength. Four specimens of SRP paper of different additive labels S0 (no additive), S1 (starch and KOH), S2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…In paper making, low apparent density (high porosity) arises due to the long and stiff fibers, insufficient refining, absence of fillers and fines, insufficient or no calendaring, and their combinations, which could explain the low apparent density of handmade papers. Low apparent density in the range of 0.2–0.5 g/cm 3 was also reported in laboratory-made handmade paper samples. ,, …”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…In paper making, low apparent density (high porosity) arises due to the long and stiff fibers, insufficient refining, absence of fillers and fines, insufficient or no calendaring, and their combinations, which could explain the low apparent density of handmade papers. Low apparent density in the range of 0.2–0.5 g/cm 3 was also reported in laboratory-made handmade paper samples. ,, …”
Section: Resultssupporting
confidence: 55%
“…Low apparent density in the range of 0.2–0.5 g/cm 3 was also reported in laboratory-made handmade paper samples. 6 , 10 , 11 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, based on physical properties, fiber characteristics, and chemical composition, it was concluded that S. grossus , C. rotundus , and T. angustifolia are suitable candidates for handmade papermaking. Similarly, Mejouyo et al (2020) discussed the production and characterization of biodegradable handmade paper obtained from Sida rhombifolia plant cellulose. The paper was prepared by a traditional method called “Kraft method,” and thereafter, physical characterization was evaluated, viz ., tensile properties (Young’s modulus, elongation at break, and stress at break), water, moisture absorption rate, etc.…”
Section: Introductionmentioning
confidence: 99%